THE IMPLEMENTATION OF LABIRIN BOARD GAME IN ENHANCING STUDENTS’ SPEAKING SKILL IN ELEVENTH GRADE AT SMA NEGERI 18 MAKASSAR - A.Tri Ayu Utami Ibrahim; Nurfaizah Sahib; Restu Januarty Hamid (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
Tri Ayu Utami Ibrahim. 2022. The Implementation of Labirin Board Game in Enhancing Students' Speaking Skill in Eleventh Grade at SMA Negeri 18 Makassar, Skripsi for English Education Study Program Faculty of Teacher Training and Education University of Bosowa. (Supervised by Nurfaizah Sahib, and Restu Januarty). This research focuses on the students’ speaking skill through labirin board game. The aim of this study was to find out weather there was an enhancement of students’ speaking skill after implementing the labirin Board Game in eleventh grade at SMA 18 Makassar in the 2022/2023 academic year. The method used in this study was quantitative experimental research with one group pre-test-post-test research design. Speaking test used as the instruments of elicting the data. The procedure of collecting data was pre-test, treatment, and post-test. The samples of this research were the eleventh grade with 36 students. Simple random sampling was a method used to select a sample . The results of data analysis showed there was an enhancement in students' speaking skill of vocabulary, pronunciation, and fluency through the implementation of the abirin Board Game. The mean score of the students increased from 5.06 on the pre-test to 7.67 on the post-test The difference between the pre-test and the post-test was statistically significant (0.00<0.05). Based on the results of data analysis, the writer conclude that there was an enhancement after implementing the labirin Board Game on speaking skill in eleventh grade at SMA 18 Makassar.